1994
DOI: 10.1177/146642409411400107
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Admissions of Rural African Patients to Murchison Hospital, Natal, South Africa

Abstract: An analysis has been made of causes of admission of black patients in 1991 to Murchison Hospital, Port Shepstone, Natal. Of 6675 total admissions, 6329 (95%) were classifiable. Of the latter, 1462 (23%) were aged 12 years and-younger, namely, 763 boys and 699 girls. Their chief causes of admission were pneumonia, gastroenteritis, trauma, acute glomerular nephritis, and malnutritional diseases. Of 4867 adults (73%), 1536 were males and 3331 females. Among men, chief causes were tuberculosis, congestive cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…In four studies, all of which were conducted in rural areas, Medical Officers served as the highest cadre of medical staff (29, 34, 40, 44). In two studies, the level of training of the staff at the hospitals involved was not reported (45, 46).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In four studies, all of which were conducted in rural areas, Medical Officers served as the highest cadre of medical staff (29, 34, 40, 44). In two studies, the level of training of the staff at the hospitals involved was not reported (45, 46).…”
Section: Resultsmentioning
confidence: 99%
“…In three studies, autopsies were performed on more than 50% of deaths (30, 43, 49). Only one study carried out in a rural hospital had advanced diagnostic facilities thus limiting the range and accuracy of diagnoses for rural studies (40). …”
Section: Resultsmentioning
confidence: 99%
“…Reviews of studies of hospital admissions and postmortems in different countries have concluded that coronary heart disease and stroke were negligible in the 1950s and 60s 6-8. More recently, stroke may be emerging as an important cause of death9 and disability10,11 whereas coronary heart disease appears to have shown only a modest increase and may still be uncommon 12,13. Lifestyle surveys among black South Africans however indicate that many populations have a moderate to high prevalence of cardiovascular risk factors, including hypertension, total cholesterol, smoking (especially in men), diabetes, and obesity (especially in women) 12,14,15…”
Section: Introductionmentioning
confidence: 99%
“…Papers in scientific journals on burden of disease as reflected by hospital admissions did not return any relevant information; pellagra was not named among the leading ten or twenty causes of admission (93)(94)(95)(96)(97)(98)(99)(100)(101)(102) . Most of these papers covered hospitals serving disadvantaged communities, where malnutrition, and therefore pellagra, would have been the most prevalent.…”
Section: Estimations From Burden Of Disease Based On Hospital Admissions and Causes Of Deathmentioning
confidence: 99%